Real-time Sensing and Visualization of Electromagnetic Situation Based on Multi-source Information Fusion. Issue 1 (March 2021) - Huang, Hanyan; Cao, Te; Chen, Hongbo; Wang, Jinbo
Abstract: It is of great significance for real-time sensing and visualization of electromagnetic situation to grasp the battlefield situation. The most important procedure is to deal with multi-source mass electromagnetic perception data and realize the point to space electromagnetic situation data refactoring. The basic idea of this paper is to estimate the electromagnetic field intensity of any concerned position by space domain fusion of multi-source data fusion after time domain fusion. Firstly, the Grubbs criteria is used in the pretreatment of single sensor data, and then the Bootstrap re-sampling methods is used for single sensor information fusion. This method can eliminate the vagueness and uncertainty of a mass of sensing data in a short period of time. Secondly, by the D-S evidence theory, the multi-sensor perceptual data combined with the wave propagation model and expert information are fused, and finally the prediction of space electromagnetic situation data is reconstructed. Finally, calculation examples of single sensor fusion and multi-sensor fusion are given to illustrate that the developed methods can increase the credibility of the reconstructed electromagnetic situation.